Positive Psychology Practices in Muslim Communities: A Systematic Review - Anlı, Gazanfer (Journal of religion and health, 2025)
Psychology's positive subfield emphasizes human well-being by concentrating on the strengths, virtues, and elements that promote it, as opposed to focusing solely on mental illness and disadvantage. Positive psychology interventions have gained international recognition, but their application and impact in non-Western societies, especially within Muslim communities, have not been thoroughly examined. Integrating positive psychology into psychotherapy practices within the Muslim community involves a distinctive blend of cultural, religious, and psychological factors. Practicing positive coping mechanisms through prayer and social support from the community is associated with better mental well-being. This study was carried out with the aim of providing a synthesis of articles on the practice of positive psychology in Muslim communities. Based on the search strategy as well as inclusion and exclusion criteria, four studies were chosen for further examination. These studies encompassed a wide range of populations, such as nurses and university students in Indonesia, humanitarian workers in the Philippines, and students in Malaysia. Participants across these four studies reported improvements in their psychological well-being, including heightened happiness, decreased stress levels, and increased post-traumatic growth as a result of positive psychology and Islamic-influenced approaches. This study provides a comprehensive analysis of the impact and cultural appropriateness of positive psychology interventions among Muslim populations. It seeks to pinpoint optimal methodologies and potential avenues for further investigation by reviewing multiple existing studies.